Necessity of direct energy and ammonium recovery for carbon neutral municipal wastewater reclamation in an innovative anaerobic MBR-biochar adsorption-reverse osmosis process - Zhang, Xiaoyuan (2022)
With the speedy evolution of global climate change and water shortage, there is a growing need for the energy and carbon neutral wastewater reclamation technology. To tackle this challenge, an innovative anaerobic membrane bioreactor (AnMBR)-biochar adsorption-RO process was developed for reclaiming municipal wastewater to high-grade product water with the aims for achieving the energy and carbon neutrality. It was found that about 95.6% of influent COD was removed by AnMBR with direct generation of biomethane, while ammonium-N in AnMBR permeate was fully recovered through biochar adsorption. The effluent from biochar adsorber with significantly lowered divalent ions concentrations was further reclaimed by RO at reduced cost and energy consumption. The energy demand and the total carbon emissions in the proposed process were estimated to be 0.50 kWh/m3 and 633 g CO2e/ m3 against 0.86 kWh/m3 and 1101 g CO2e/ m3 in the current conventional activated sludge (CAS)-microfiltration-RO process. It was further shown that the ammonium recovery via biochar adsorption could offset about 0.503 kWh/m3 that was originally utilized for chemically producing recovered ammonia by the Haber-Bosch method, equivalent to a carbon offsetting of 498 g CO2e/m3, leading to a net carbon emission of 135 CO2e/m3 in the proposed process, which was only about 12% of that in the current CAS-MF-RO process. These suggested that a carbon-neutral municipal wastewater reclamation might be achievable through concurrent carbon reduction and offsetting, while carbon offsetting via ammonia recovery appeared to be a game-changer towards the carbon-neutral operation. Consequently, it is expected that this study can shed lights on how energy- and carbon-neutrality would be achieved by innovating municipal wastewater reclamation technology.